2005
DOI: 10.1007/s10633-005-7350-0
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Medication Effects on the Pattern Visual Evoked Potential*

Abstract: Visual disruption in patients diagnosed with epilepsy may be attributable to either the disease itself or to the anti-epileptic drugs prescribed to control the seizures. Effects on visual function may be due to perturbations of the GABAergic neurotransmitter system, since deficits in GABAergic cortical interneurons have been hypothesized to underlie some forms of epilepsy, some anti-epileptic medications increase cortical GABA levels, and GABAergic neural circuitry plays an important role in mediating the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Flash VEP is now well established in the diagnosis of multiple sclerosis 76 and epilepsy 29 . VEPs measure the electrophysiological responses of the anterior visual pathway to flash and checkerboard visual stimuli.…”
Section: Assessment Of the Visual Pathway In The Unresponsive Patientmentioning
confidence: 99%
“…Flash VEP is now well established in the diagnosis of multiple sclerosis 76 and epilepsy 29 . VEPs measure the electrophysiological responses of the anterior visual pathway to flash and checkerboard visual stimuli.…”
Section: Assessment Of the Visual Pathway In The Unresponsive Patientmentioning
confidence: 99%
“…Since the first use of the white-black chessboard reversal pattern and the grating pattern to study vision and the revealing of tight correlations between components of the VEP and visual acuity [1,2] , researchers have attempted to apply the technique to clinical evaluation and ophthalmological assessment [3][4][5] . Because of the method-ological advantages of VEPs (simple waveform, repeatability, and small inter-individual variation), increasing attention has been paid to the study of diseases involving visual problems, such as in the field of oculopathy (amblyopia [6,7] , refractive errors, field defects, diseases of the optic nerve, glaucoma [8] and color blindness), in diseases with latent impairment of vision (multiple sclerosis [9] , diabetes [10] ), and in psychological dysfunctions (schizophrenia, dementia, epilepsy) [11][12][13][14] . So far only some changes in the early components (especially the P100) have been associated with certain diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same paradigm, Sundqvist et al (1999) also found no effect on the VEP in 16 juvenile myoclonic epilepsy patients treated with VPA monotherapy at 1000mg and 2000mg/day for 6 months each. Using an on-off SSVEP paradigm, Geller et al (2005) found no effect of VPA on the second harmonic amplitude in generalized epilepsy compared to healthy controls. In contrast to the above, amplitude of the flash VEP in photosensitive epilepsy patients decreased following treatment with VPA (Herrick and Harding, 1980).…”
Section: Discussionmentioning
confidence: 81%
“…In a group of patients with unspecified epilepsies on monotherapy with carbamazepine, levetiracetam, or VPA, no significant change was observed in P100 amplitude compared to healthy controls not taking medications (Tumay et al, 2013). Carbamazepine had no effect on SSVEP amplitude compared to healthy controls not taking any medication (Geller et al, 2005). In a group of 30 focal and generalized epilepsy patients, monotherapy using phenytoin, carbamazepine, or phenobarbital did not change the latency or amplitude of P100, but polypharmacy decreased the amplitude and increased latency (Drake et al, 1989).…”
Section: Discussionmentioning
confidence: 99%